Analysis of Library School Syllabi Reveals Poor Design and Limited Content about Disability and Accessibility / Pionke, J. (2023). What are library graduate students learning about disability and accessibility? A syllabus analysis. Urban Library Journal, 29(1). https://academicworks.cuny.edu/ulj/vol29/iss1/2/ - Prince, Nandi (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2024)
Objective – To analyze the disability and accessibility content of library sciences courses. As well as to determine the importance of teaching students about this topic throughout programs covered in the study.Design – Qualitative study involving the data analysis of syllabi.Setting – Selected library graduate school curriculum programs in the United States.Subjects – In total, 77 syllabi drawn from 49 institutions taken from the American Library Association listing of accredited library school graduate programs.Methods – The author used keyword searches to identify courses offered between 2017–2020 that contained content on disability and accessibility. Syllabi were available for 77 of the 145 identified courses. The author analyzed the sample set (n=77) for both content and structure.Main Results – Poor citation structure, disability accommodation statements, assessment, and a focus on digital accessibility were among the main findings highlighted. The author identified four major categories to explain and understand the content found on the syllabi; these descriptors were further broken down into sub-categories to explain the findings of each topic content area. Highlights of the results are:(1) disability and accessibility topics and all related terms were ranked according to number of times they appeared, e.g. digital content, usability, web/internet, coding (22); instruction and information literacy (16); and specific demographics etc. (10);(2) the organization and sequencing of when course content was presented - at the beginning, middle and end of the semester;(3) citation currency– Two hundred syllabi were analyzed. One hundred and forty-one syllabi had fairly current citation dates falling between 2009-2018. Forty-eight had no dates and eleven had dates that were outdated (2008 or earlier);(4) assignments – which measured the learning outcome of the said topic were reported in the following way: nothing assigned (67); 1 or more assignments (11); undetermined (3).Conclusion –The study underlies that a well-crafted syllabus effectively communicates the goals of the course – the importance of the topic structure about disability and accessibility in library schools’ curricula. The author identified numerous design flaws that impact how the content relays information about the course’s pedagogy. The data suggest the need for the following improvements on the syllabi: professional topic presentation, variety of formats in texts and materials and their access, citation currency and poor structure, assignments and organization sequencing of course content, a number of assessment focused observations on vague assignments or lack of examples provided, and the inclusion of disability statements. Some of the higher order concerns were: the ableist language contained, outdated language, and the lack of stated university-related disability resources for students. All of the aforementioned present an accessibility barrier for disabled students and may affect the general perception about the topic. The author recommends that stronger guidelines for LIS educators would be advantageous to students, encourage disability awareness and the best DEI practices. Further to this, libraries should implement and adapt a strategic plan that would help overcome accessibility barriers for patron delivery services. There must be an increased emphasis on teaching about accessibility that expands beyond forms of digital media. Providing equitable library services in all areas for the disabled populations in the physical library spaces is needed.